Genetic variability for root, shoot and water use efficiency traits in castor (Ricinus communis L.): GENETIC VARIABILITY FOR WATER USE EFFICIENCY TRAITS IN CASTOR - P LAKSHMAMMA; LAKSHMI PRAYAGA; C SARADA (Journal of Oilseeds Research, 2013)
A study was conducted to identify castor (Ricinus communis L.) genotypes with good root growth for water mining, high total drymatter(TDM) and high water use efficiency (WUE). Sixty four genotypes including germplasm lines and advanced varietal/hybrid trial(AVT/AVHT) entries were sown during rainy season of 2008 in two specially constructed rootstructures(32 in each structure)replicating twice with four plants/replication after attaining the bulk density of the structure asthat offield . Data on root (length, volume, dry weight),shoot (leaf area index, TDM,stem girth) and WUE traits (SPAD chlorophyll meter reading, specific leaf area, 13C, 18O) were recorded at 90 DAS. Efficient genotypes were selected based on a composite index using principal component analysis (PCA) and top 10 genotypes were selected for root and shoot growth traits. These genotypesinclude RG 1437, RG 1463, RG 1494, RG 1614, RG 1645, RG 1941, RG 2058, RG 2113, RG 2127 and RG 2139.